Effects of workers motivation on construction productivity / Adebowale Oluseyi J. and Fapohunda Julius Ayodeji - Adebowale, Oluseyi J.; Fapohunda, Julius Ayodeji (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
The issue of construction workers motivation becomes a subject of debate among construction project management professionals. Therefore, there are diverse opinions on whether motivation of construction workers positively impacts construction workers performance or rather adversely affects the general performance of construction labours. This brings about different motivation concepts and principle by researchers towards improvement of construction workforce performance. The paper takes into cognisance the perception of construction practitioners on motivation in relation with construction productivity towards achieving construction project objectives. In order to obtain a viable result of the study, the study adopts quantitative research approach on construction workforce motivation with project managers, contract managers, site managers, contractors, and site supervisors. Quantitative data obtained was analysed with SPSS statistical tools. The perception of construction practitioners was explored on motivation drives of construction workforce. However, it was found that motivation is important for construction workers performance, giving bonus to workers is important to improve workers efficiency and there is a need for construction workers recognition by management. The adequate application of recommendation of this study will enhance construction labour productivity, reduce wastes in construction, improve general construction performance and ultimately heightens customer's satisfaction.